Masalah Terjemahan Kata Syu’arā’ sebagai Para Pemusik: Kajian Semantik - Achmad Tito Rusady; Muhammad Thoriqussu’ud; Amien Ashiddiqi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The problem of translating the word شعراء/syu’arā’ into para pemusik has caused reactions from various groups, including the MUI (Indonesian Ulema Council). To unravel this problem, translation accuracy is needed through semantic triangle (meaningful triangle) and the achievement of weltanscaaung (worldview of the language owner) in the semantic study of Toshihiko Izutsu. This study uses a descriptive qualitative approach, with primary data obtained from the dictionary Lisan Arabi, the Tafsir Ruhul Ma’ani and the Tafsir of Zamakhsyari. The results of this study found that the problem of translating the word syu’arā’ into para pemusik is a fatal type of problem, because the concept meaning/fikrah angle in semantic triangle does not reach weltanschauung. The process of tracing the achievement of the weltanschauung of the word syu'arā' was carried out in 3 stages; 1) searching for basic meaning, 2) searching for relational meaning, and 3) searching for historical meaning. These three stages found that the meaning of syu'arā' is people who express words that are beautifully arranged in wazn and qafiyah, who are insightful and imaginative. This study proves that the correct translation of the word syu’arā’ is ‘para penyair’ not ‘para pemusik’. This study contributes to providing an accurate translation of the words syi’ir/شعر and syā’ir/شاعر in Indonesian.